PEMERIKSAAN MIKROSKOP DAN TES DIAGNOSTIK CEPAT DALAM MENEGAKKAN DIAGNOSIS MALARIA - Kusuma, Wijaya; Lestari, A.A. Wiradewi; Herawati, Sianny; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana, 2014)
Malaria is an infection disease caused by plasmodium parasite that transmitted to human body by female anopheles mosquito bites. World Health Organization ( WHO) predicted that 3,3 billion people around the world were at risk to infected by malaria in 2006 and almost 1 million died because of this disease. Diagnosis of malaria according to clinical manifestation only is not specific; therefore it is less reliable and should be s upported by laboratory examination result. Microscopic examination of blood smear and rapid diagnostic test are most often used to diagnose malaria. Both of this test gave big chance to make accurate diagnostic but still have their own limitations.
Keywords: Malaria, microscopic examination, rapid diagnostic test